The Future of the Quran’s Role: Digitalizing versus Memorizing in the Southeast Asian Muslims - Munzir Hitami (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article is intended to analyze the role transmutation of religion occurred in the religious community in South-east Asia, especially in the Muslim community. Religion personally and collectively is usually believed as a form of the human obedience to the Almighty. Many activities either individual or collective are considered as manifestation of belief or implementation of God’s orders that the scripture contained. Often reading religious scripture like the Qur’an inspirited some radical groups to spread intimidation and violence for realization of their goal as be seen in several late decades. Meanwhile there are interesting phenomena take place in the Muslim community i.e. increasing memorization of the Quran besides its digitalization. In consequent, the former will emerge a generation of memorizers (ḥuffāⱬ) and the latter will facilitate the non-memorizers to deal easily with their holy book as such. Then, what is likely the impact of these phenomena in the future of the Muslim life. Are they will dominantly enhance radicalization or de-radicalization or other impact in accordance with development of technological and industrial era that so called the 4.0 era or the 5.0 era.